2005
DOI: 10.1126/science.1118829
|View full text |Cite
|
Sign up to set email alerts
|

Coincident Scrapie Infection and Nephritis Lead to Urinary Prion Excretion

Abstract: Prion infectivity is typically restricted to the central nervous and lymphatic systems of infected hosts, but chronic inflammation can expand the distribution of prions. We tested whether chronic inflammatory kidney disorders would trigger excretion of prion infectivity into urine. Urinary proteins from scrapie-infected mice with lymphocytic nephritis induced scrapie upon inoculation into noninfected indicator mice. Prionuria was found in presymptomatic scrapie-infected and in sick mice, whereas neither prionu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(126 citation statements)
references
References 16 publications
7
116
1
2
Order By: Relevance
“…However, there are studies that are not consistent with these findings (26,27). Perhaps unrecognized nephritic conditions may underlie these discrepant observations, because it has been reported that urinary prion excretion is found only in scrapie-infected mice with lymphocytic nephritis (28). In this study, we observed several bands with high molecular weights that reacted with anti-cheetah AA antiserum in the whole urine sample, but not in the urine pellet in which AA amyloid fibrils should be recovered.…”
Section: Discussionmentioning
confidence: 55%
“…However, there are studies that are not consistent with these findings (26,27). Perhaps unrecognized nephritic conditions may underlie these discrepant observations, because it has been reported that urinary prion excretion is found only in scrapie-infected mice with lymphocytic nephritis (28). In this study, we observed several bands with high molecular weights that reacted with anti-cheetah AA antiserum in the whole urine sample, but not in the urine pellet in which AA amyloid fibrils should be recovered.…”
Section: Discussionmentioning
confidence: 55%
“…Quantification was performed on a Storm PhosphorImager System (Amersham Biosciences). Antibodies used were as follows: 3F4 monoclonal anti-PrP antibody (Signet Laboratories) at 1:2500; POM1 anti-PrP antibody (25,26) Immunohistochemical Staining-The tissue processing for immunohistochemical staining was performed as described previously (19). The anti-cPLA 2 antibody (Santa Cruz Biotechnology) was used at 1:50.…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps multiple exposure pathways can lead to an infection, nevertheless, horizontal spread of CWD is clearly Inflammation may increase the risk of prion shedding in cervids. In prion-infected mice, follicular inflammation in the kidney directs prions to accumulate within lymphoid follicles [21] and intriguingly, leads to prion excretion into the urine of infected mice [22]. Even in natural sheep scrapie cases, follicular mastitis results in prion accumulation in the mammary gland [23].…”
Section: Transmission Among Cervidsmentioning
confidence: 99%